Peran Bawaslu Kota Medan dalam Meminimalisir Kecurangan Pilkada 2024 (Studi Tentang Keberhasilan dan Tantangan) - Windi Adelia Saragih; Abu Syahrin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Regional elections are a crucial component of Indonesia’s democratic system, allowing citizens to choose local leaders and influence regional policies. However, the integrity of these elections often faces challenges from electoral fraud, such as vote buying, digital misinformation, and weak regulatory frameworks. This study aims to analyze the role of the Medan City Election Supervisory Committee in minimizing electoral fraud during the 2024 Pilkada. Using a qualitative case study approach, the research explores the effectiveness of Bawaslu’s supervision strategies and the obstacles encountered in ensuring fair and transparent elections. Data were collected through in-depth interviews, direct observation, and analysis of official documents. The findings reveal that although Bawaslu has made significant efforts in voter education and inter-agency coordination, several challenges persist, including limited human resources, low digital literacy among voters, and insufficient legal provisions to address digital campaign violations. The study also highlights the importance of public participation and collaboration with civil society in strengthening electoral supervision. Furthermore, the integration of technology such as AI and data analytics is recommended to enhance Bawaslu’s monitoring capacity. This research provides practical insights and recommendations for improving electoral oversight mechanisms and promoting democratic integrity in local elections, particularly in the digital era. It is hoped that this study can contribute to more credible and inclusive democratic practices in Indonesia.